Die Region Schlesien (1618–1740). Die sozialen Gruppierungen und ihre Bedeutung für die Identität des Landes - Herzig, Arno (Wydawnictwo eBooki.com.pl, 2014)
The social groups of Silesian society in the 17th century included higher nobility (dukes, estate lords, foremen) and lower nobility, to which, due to ennoblements ascended many of the townspeople. Among the townsfolk in Silesian cities were such groups as merchants, guild craftsmen and people with higher education. They had civic rights. Most of city-dwellers did not have civic rights, they were the daily wage labourers, guild-less craftsmen, farmhands and servants. Village-dwelling population was divided into peasant classes, the majority of which were the lower peasants, so-called gardeners, who owned little land and livestock and in order to assure their survival needed to seek additional employ (as village craftsmen, workers on farms or estates). A place in the hierarchy was assured not by an initial economic capital, but rather by symbolic capital. The group that influenced Silesian regional identity the most were educated townspeople, whose roots were in humanism.
Keywords: identity; Silesian estates; social groups; humanism; status symbol; symbolic capital; power and authority